1997
DOI: 10.1016/s0896-6273(00)80401-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in Fast Synaptic Inhibition of Adult Oxytocin Neurons Caused by Switch in GABAA Receptor Subunit Expression

Abstract: We found that magnocellular oxytocin neurons in adult female rats exhibit an endogenous GABA(A) receptor subunit switch around parturition: a decrease in alpha1:alpha2 subunit mRNA ratio correlated with a decrease in allopregnanolone potentiation and increase in decay time constant of the GABA(A) receptor-mediated IPSCs in these cells. The causal relationship between changes in alpha1:alpha2 mRNA ratio and the ion channel kinetics was confirmed using in vitro antisense deletion. Further, GABA(A) receptors exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
195
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 65 publications
(30 reference statements)
19
195
0
Order By: Relevance
“…While mIPSCs in magnocellular neurons displayed a high-frequency, large peak amplitude and fast decay, parvocellular neuron mIPSCs were low in frequency, had a small peak amplitude, and were more slowly decaying. The mIPSC characteristics for magnocellular neurons as found in this study closely resemble those described for magnocellular neurons in the SON (Brussaard et al 1997). The higher frequency of mIPSCs in magnocellular neurons may be related to the fact that the percentage of inhibitory synapses making contact with the soma is higher in the magnocellular than the parvocellular region, as established with electronmicroscopy (Decavel and Van den Pol 1990).…”
Section: Characterization Of Pvn Neuronssupporting
confidence: 82%
See 1 more Smart Citation
“…While mIPSCs in magnocellular neurons displayed a high-frequency, large peak amplitude and fast decay, parvocellular neuron mIPSCs were low in frequency, had a small peak amplitude, and were more slowly decaying. The mIPSC characteristics for magnocellular neurons as found in this study closely resemble those described for magnocellular neurons in the SON (Brussaard et al 1997). The higher frequency of mIPSCs in magnocellular neurons may be related to the fact that the percentage of inhibitory synapses making contact with the soma is higher in the magnocellular than the parvocellular region, as established with electronmicroscopy (Decavel and Van den Pol 1990).…”
Section: Characterization Of Pvn Neuronssupporting
confidence: 82%
“…These criteria are based on earlier studies, describing mIPSC properties in other hypothalamic nuclei or other brain areas (Brussaard et al 1997;Wierenga and Wadman 1999). Based on these criteria about 14% of all initially mIPSC detected events were discarded, equally distributed over the different treatment groups.…”
Section: Recordings and Analysismentioning
confidence: 99%
“…Brussaard and colleagues (1997) have shown that that high concentrations of allopregnanolone (1 -10 μM) prolong sIPSC decay and diminish action potential firing in magnocellular neurons from the SON of juvenile female rats and that this modulation also depends upon a G protein/ PKC-dependent mechanism. Remarkably, in contrast to juvenile females, the potentiating effect of allopregnanolone on GABAergic sIPSCs and its inhibitory effect on action potential firing were found to be absent or markedly reduced in parturient or postpartum females (Brussaard et al, 1997). The change in allopregnanolone at the time of parturition was attributed to enhanced PKC activation and phosphorylation of postsynaptic GABA A receptors arising from oxytocin receptor-mediated signaling .…”
Section: Steroid Modulation Of Gabaergic Transmission In Hypothalamusmentioning
confidence: 86%
“…Using this methodology, allopregnanolone concentrations in cortical homogenates were estimated to be ~1-2 ng/g in juvenile, ~1 ng/g in diestrous, 4-6 ng/g in estrous, and 4-8 ng/g in proestrous females, with levels reaching ~10-30 ng/g during pregnancy (Paul and Purdy, 1992;Corpéchot et al, 1993;Concas et al, 1998;Kellogg and Frye, 1999). These assessments have been used to estimate that allopregnanolone levels are diestrus females (Paul and Purdy, 1992), but can reach ~100 nM during the late stages of pregnancy (see for example; Brussaard et al, 1997;Lambert et al, 2003). The androgenic neurosteroid, 3α-diol, also showed cycle-dependent variation in cortical homogenates, with levels being lowest in diestrus I (0.08 ng/g) and rising steadily as the cycle progresses to a maximum of 0.33 ng/g during estrus (Kellogg and Frye, 1999).…”
Section: Neurosteroid and Anabolic Androgenic Steroid Levels In The Cnsmentioning
confidence: 99%
See 1 more Smart Citation